Analysis of Parameters Influencing Swimming Ability of Crucian Carp Based on Numerical Simulation - Wenhua CHU; Qing YUN; Huiqin GUO; Shulong WU; Zhong ZHANG (工程科学与技术, 2024)
The mechanisms of fish swimming behavior and the factors influencing swimming ability are pivotal in current research on fish bionomics. The Crucian carp, a typical Carangiform swimmer, is selected as the subject of this study. A numerical simulation method, dynamic grid technology, and User–Defined Functions (UDF) are employed to investigate the effects of motion parameters, fish body size, and swimming environment (wall boundary) on the swimming ability of Crucian carp. This study measures the swimming ability by the time it takes for the bionic carp to achieve a dynamic and stable cruising speed. The findings indicate that when the fluctuation frequency ranges from 0.07 to 5.50, and the amplitude factor is between 0.03 and 0.06, an increase in frequency and amplitude results in a reduction in the time required for the bionic carp to reach a dynamic stable cruising velocity, which also increases the cruising velocity. Dimensionless numerical calculations are performed on Crucian carp with varying thickness-to-length ratios and body lengths. It is determined that body size is inversely proportional to swimming velocity when swimming forward with consistent swing amplitude and frequency. A higher cruising velocity is achieved when the thickness-to-length ratio is less than 0.166. Regarding body length L, juvenile carp can reach the cruising stage more rapidly but exhibit a lower cruising velocity of about 0.6L s–1. The speed of the bionic young fish is more pronounced during the acceleration stage, and the cruising stage mirrors the dynamic stable cruising velocity of the bionic adult fish, which is approximately 1L s–1. The presence of walls near which the fish swim can diminish the swimming velocity. The impact of bilateral walls on the swimming velocity of bionic carp is more substantial than that of unilateral walls; when the fish body is 0.5L from a unilateral wall and 0.8L from bilateral walls, it is not affected by the wall. These results can provide a valuable reference for research in fish bionomics.